Mengembangkan Strategi Untuk Meningkatkan Minat Konsumen Terhadap Fashion Halal di Indonesia Melalui Optimalisasi Rantai Pasok Halal - Nur Rahmi Irfaniah; Puji Purnawan (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
Halal fashion in Indonesia continues to experience significant growth along with the increasing Muslim population and awareness of sharia-compliant values. This study aims to analyze strategies to increase consumer interest in halal fashion using the Framework for Chain/Network Development (FCD) approach. Quantitative methods are used, collecting primary data from Muslim consumers in five major cities. The main findings reveal that logistics control and supply chain resources significantly influence consumer interest, while halal policies and supply chain performance do not show the same effect. An integrated and transparent supply chain is a key element in building consumer trust, supported by the application of technologies such as blockchain to improve traceability and efficiency. This study provides practical guidance for industry players in designing a sharia-compliant supply chain and strategic policy recommendations to support the halal fashion industry's aspirations. With a focus on logistics control and resource optimization, Indonesia has the potential to become a global halal fashion hub.